Artificial Intelligence and Machine Learning in CRM: Leveraging Data for Predictive Analytics (Journal of Artificial Intelligence & Research, 2024)
Companies that have captured the skill of determining whatever the customer might need or want at any particular moment are successful in today's dynamic business world. The central duties include managing and building relationships with customers; this is where CRM comes in. But with AI and ML, there is a change. The efficiency has, however, incremented by bounds and leaps, and now CRM can process vast amounts of data about customers, coming up with insights on which to base decisions for more personalized experiences.The article highlights the transformative role of AI and ML in CRM, notably how these technologies enable predictive analytics. Using the power of AI and ML, predictive analytics permit a business to accurately forecast customer behaviors, segment audiences with extreme accuracy, and tailor interactions to individual tastes, increasing customer satisfaction and brand loyalty. AI-powered CRM can use data from customer contact histories together with external information sources to predict future trends, show which clients are at risk, adapt sales strategy, and enhance marketing campaigns.The applications of AI and ML in CRM, like sales forecasting, customer-churn prediction, and lead scoring, have been taken up for analysis in this article. It explains how all these innovations are contributing towards better customer relationship management. This also covers the challenge in integration of Artificial Intelligence and Machine Learning into the existing CRM system, including data quality and ethical concerns and the cost of implementation.Today, businesses are still fighting their way out to survive in an increasingly digital environment. The importance of its application in leveraging AI and ML in CRM is only going to increase. The current paper elaborates on the current status and future direction of AI-driven CRM systems and provides useful guidance for organizations that intend to effectively harness the power of predictive analytics to stay ahead in the marketplace.